2012
DOI: 10.1002/term.1467
|View full text |Cite
|
Sign up to set email alerts
|

Teratoma formation of human embryonic stem cells in three-dimensional perfusion culture bioreactors

Abstract: Teratoma formation in mice is today the most stringent test for pluripotency that is available for human pluripotent cells, as chimera formation and tetraploid complementation cannot be performed with human cells. The teratoma assay could also be applied for assessing the safety of human pluripotent cell-derived cell populations intended for therapeutic applications. In our study we examined the spontaneous differentiation behaviour of human embryonic stem cells (hESCs) in a perfused 3D multi-compartment biore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…The cells underwent self-selection to form aggregates and initiate the first step of chondrogenic differentiation - the cell condensation. Formation of pellets also helped the formation of more homogenous cell aggregates compared to the heterogeneous EBs, which are characterized by gastrula-like tissues with varying local concentrations of morphogenic factors [4345]. At 6 weeks, chondrogenic pellets derived from transient hypoxia EBs (Group 4) exhibited an excellent homogeneity, which could partially be attributed to the loss of unspecified cells remaining in cell suspension and washed away during medium changes in pellet cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The cells underwent self-selection to form aggregates and initiate the first step of chondrogenic differentiation - the cell condensation. Formation of pellets also helped the formation of more homogenous cell aggregates compared to the heterogeneous EBs, which are characterized by gastrula-like tissues with varying local concentrations of morphogenic factors [4345]. At 6 weeks, chondrogenic pellets derived from transient hypoxia EBs (Group 4) exhibited an excellent homogeneity, which could partially be attributed to the loss of unspecified cells remaining in cell suspension and washed away during medium changes in pellet cultures.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that this 3D bioreactor system supports stable culture of PHH under serum-free conditions 24,25 and is suitable for differentiation of human embryonic stem cells (hESC). 26,27 …”
Section: Introductionmentioning
confidence: 99%
“…To address this, animal-free in vitro methods of teratoma formation are being explored. One recent study examined the spontaneous differentiation of human ES cells in a perfused three-dimensional multi-compartment bioreactor [24]. This system reported generation of embryoid bodies with histological and transcriptional features similar to those that develop in the mouse teratoma assay.…”
Section: Xeno-free Human Pluripotent Stem Cell Characterisationmentioning
confidence: 99%